(untitled) (Analysis in Theory and Applications, 2024)
In the paper, the authors introduce the Orlicz space corresponding to the Young function and, by virtue of the equivalent theorem between the modified K-functional and modulus of smoothness, establish the direct, inverse, and equivalent theorems for the linear combinations of Jacobi weighted Baskakov–Durrmeyer operators in the Orlicz spaces.